QUALITY OF FROZEN SHEEP SPERM USING SOYBEAN LECITHIN EXTENDER - Salmin; Marsudi; Hendro Sukoco (Wahana Peternakan, 2023)
The study aimed to study the impact of optimum levels of soybean lecithin in Tris extenders on the quality of frozen sheep sperm. The observed variable was the quality of the post-freezing spermatozoa, which covers the progressive motility, viability, abnormality and integrity of the sperm membrane. The results of the study showed that the level of lecithin in soybeans had a real influence (P<0,05) on all parameters of the quality of post-freezing sheep spermatozoa. The higher the level of soybean lecithin, the higher the percentage of progressive motility, viability, integrity of sperm membranes up to 3% soybean lecithin, then a decrease of 4% soybean lecithin and decreasing sperm abnormality percentages to 3% Soybeans Lecithin. The Average percentage of progressive motility (43.79%), viability (50.85%) and membrane integrity (51.65%) of post-freezing spermatozoa treated with 3% soya bean lecithin (L3) was significantly higher (P<0.05), and sperm abnormalities (13.72%) were significantly lower (P <0.05) than all treatments tried. Keywords: Membrane integrity, Motility, Frozen spermatozoa Quality, Soybean lecithin